Monosubstituted tricationic Zn(II) phthalocyanine enhances antimicrobial photodynamic inactivation (aPDI) of methicillin-resistant Staphylococcus aureus (MRSA) and cytotoxicity evaluation for topical applications: in vitro and in vivo study. Issue 1 (1st January 2020) - Dharmaratne, Priyanga; Wang, Baiyan; Wong, Roy C. H.; Chan, Ben C. L.; Lau, Kit-Man; Ke, Mei-Rong; Lau, Clara B. S.; Ng, Dennis K. P.; Fung, Kwok-Pui; Ip, Margaret
ABSTRACT: Antimicrobial photodynamic therapy (aPDT) is an innovative approach to combat multi-drug resistant bacteria. It is known that cationic Zn(II) phthalocyanines (ZnPc) are effective in mediating aPDT against methicillin-resistant Staphylococcus aureus (MRSA). Here we used ZnPc-based photosensitizer named ZnPcE previously reported by our research group to evaluate its aPDT efficacy against broad spectrum of clinically relevant MRSAs. Remarkably, in vitro anti-MRSA activity was achieved using near-infrared (NIR, >610 nm) light with minimal bactericidal concentrations ranging <0.019–0.156 µM against the panel of MRSAs. ZnPcE was not only significantly ( p  < .05) more potent than methylene blue, which is a clinically approved photosensitizer but also demonstrated low cytotoxicity against human fibroblasts cell line (Hs-27) and human immortalized keratinocytes cell line (HaCaT). The toxicity was further evaluated on human 3-D skin constructs and found ZnPcE did not manifest in vivo skin irritation at ≤7.8 µM concentration. In the murine MRSA wound model, ZnPcE with PDT group demonstrated > 4 log10 CFU reduction and the value is significantly higher ( p  < .05) than all test groups except positive control. To conclude, results of present study provide a scientific basis for future clinical evaluation of ZnPcE-PDT on MRSA wound infection.